A New Result for ψ-Hilfer Fractional Pantograph-Type Langevin Equation and Inclusions. (26th September 2022) - Lmou, Hamid; Hilal, Khalid; Kajouni, Ahmed
Abstract : In this paper, we deal with the existence and uniqueness of solution for ψ -Hilfer Langevin fractional pantograph differential equation and inclusion; these types of pantograph equations are a special class of delay differential equations. The existence and uniqueness results are obtained by making use of the Krasnoselskii fixed-point theorem and Banach contraction principle, and for the inclusion version, we use the Martelli fixed-point theorem to get the existence result. In the end, we are giving an example to illustrate our results.